2010
DOI: 10.1186/1471-2407-10-409
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Hsp90 expression in infiltrative lobular carcinoma: an immunohistochemical study

Abstract: BackgroundElevated Hsp90 expression has been documented in breast ductal carcinomas, whereas decreased Hsp90 expression has been reported in precursor lobular lesions. This study aims to assess Hsp90 expression in infiltrative lobular carcinomas of the breast.MethodsTissue specimens were taken from 32 patients with infiltrative lobular carcinoma. Immunohistochemical assessment of Hsp90 was performed both in the lesion and the adjacent normal breast ducts and lobules; the latter serving as control. Concerning H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…Contrary to the pathological findings published by our team [ 48 , 49 , 50 ], as well as by other research groups [ 45 , 46 , 47 , 51 ], according to which Hsp90 exhibits significant variability along both series, such a finding was not replicated at the level of Hsp90 serum concentrations [ 56 ].…”
Section: Hsp90 Expression In Breast Carcinogenesiscontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the pathological findings published by our team [ 48 , 49 , 50 ], as well as by other research groups [ 45 , 46 , 47 , 51 ], according to which Hsp90 exhibits significant variability along both series, such a finding was not replicated at the level of Hsp90 serum concentrations [ 56 ].…”
Section: Hsp90 Expression In Breast Carcinogenesiscontrasting
confidence: 99%
“…Elevated Hsp90 expression has been documented in breast ductal carcinomas [ 44 , 45 , 46 , 47 , 48 ], whilst a significantly decreased Hsp90 expression has been shown in infiltrative lobular carcinomas and lobular neoplasia [ 49 , 50 ].…”
Section: Hsp90 Expression In Breast Carcinogenesismentioning
confidence: 99%
“…data indicated a reduction also evident between IDC and DCIS, as well as DCIS and normal breast tissue. Especially concerning lobular lesions Zagouri et al showed a significantly lower Hsp90 expression in lobular neoplasia and invasive lobular carcinomas, compared to the noncancerous breast tissue (32,33).…”
Section: Resultsmentioning
confidence: 99%
“…The association of HSP90 gene expression with different pathological and clinical features of breast cancer has not yet been studied extensively in the novel setting of molecular subtypes of this disease. However, additionally to the suggestions that the role may be particularly associated with HER2-positive disease, there were also observations that HSP90 exhibits low expression in the lobular histotype [35].…”
Section: Discussionmentioning
confidence: 99%